(untitled) (Mustansiria Dental Journal, 2023)
Aim of the study: was to find the potential relation between the salivary concentration of matrix metalloproteinase-8 with periodontal health and disease by examining its’ level in individuals with healthy periodontium, with dental biofilm induced gingivitis and with periodontitis (localized and generalized). Material and method: Saliva was collected from 90 participants with an age range from (20-60) years, all of them were systemically healthy. 25 cases were enrolled under the dental Biofilm induced gingivitis group, 25 cases under the localized periodontitis group, and 25 cases under the generalized periodontitis group, with 15 subjects enrolled in the healthy periodontium(control) group. Detection of MMP-8 in saliva was achieved by utilizing Enzyme-Linked Immunosorbent Assay (ELISA). Results: The present data showed that MMP-8 was higher significantly(P<0.05) in disease groups (dental Biofilm induced gingivitis, localized and generalized periodontitis groups) as compared to the healthy (control) group. With a significant difference between dental biofilm-induced gingivitis and generalized periodontitis groups. Conclusion: There is a positive relationship between salivary matrix metalloproteinase-8 with periodontal health and disease.